PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN MOTOR MELALUI KEPUASAN PELANGGAN PADA PT. SURYA GEMILANG MOTOR SURABAYA - Sithiayuki, Shindy Faulia (Jurnal Manajerial Bisnis, 2024)
The purpose of this research is to test and analyze the influence of product quality, customer trust on purchasing decisions through customer satisfaction at PT. Surya Gemilang Motor, West Surabaya. Sampling method using Purposive Sampling. The scope of this research is only on variables related to product quality, customer trust which directly or indirectly influence purchasing decisions through customer satisfaction. The approach of this research is a quantitative approach method. The data analysis technique for this research uses the Partial Least Square (PLS) method with the SmartPLS 4.0 application program which includes the design process of the Inner Structural Model, Outer Structural Model and Hypothesis Testing (Resampling Bootstrapping). The research results found that there was no direct effect of product quality on customer satisfaction at PT. Surya Gemilang Motor Surabaya. There is a direct influence of Customer Trust on Customer Satisfaction at PT. Surya Gemilang Motor, West Surabaya. There is a direct effect of product quality on purchasing decisions at PT. Surya Gemilang Motor, West Surabaya. There is a direct influence of Customer Trust on Purchasing Decisions at PT. Surya Gemilang Motor, West Surabaya. There is a direct effect of purchasing decisions on customer satisfaction at PT. Surya Gemilang Motor, West Surabaya. There is no effect of Product Quality indirectly on Purchase Decisions through Customer Satisfaction at PT. Surya Gemilang Motor, West Surabaya. There is an indirect effect of Customer Trust on Purchasing Decisions through Customer Satisfaction at PT. Surya Gemilang Motor.